2018
DOI: 10.1186/s12893-018-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of children with total colonic aganglionosis: functional and metabolic long-term outcome

Abstract: BackgroundTotal colonic aganglionosis (TCA) is a rare variant of Hirschsprung’s disease occurring in 3–10% of the cases. Only few studies reported the long-term clinical and metabolic outcomes of patients with TCA. The aim of this study was to evaluate the functional and metabolic long-term outcomes of children undergoing surgical treatment for TCA.MethodsA 15-year retrospective study was performed. Blood chemistry tests and stool analysis performed at the last follow-up visit were recorded. Height and weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
9
1
15
Order By: Relevance
“…Deaths were caused by associated co-morbidities or complete aganglionosis of the bowel and, in contrast to other series 4,7,13,14 , were not directly attributable to HAEC. The overall co-morbidity rate of 26⋅9 per cent was higher than that in previous reports (4-16 per cent) 1,7,16 , and could be attributed to routine screening practices for associated malformations at tertiary neonatal surgical centres. Nearly all patients with TCA (95⋅3 per cent) were diagnosed within the first year of life, and most (76⋅4 per cent) within the first 3 months.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Deaths were caused by associated co-morbidities or complete aganglionosis of the bowel and, in contrast to other series 4,7,13,14 , were not directly attributable to HAEC. The overall co-morbidity rate of 26⋅9 per cent was higher than that in previous reports (4-16 per cent) 1,7,16 , and could be attributed to routine screening practices for associated malformations at tertiary neonatal surgical centres. Nearly all patients with TCA (95⋅3 per cent) were diagnosed within the first year of life, and most (76⋅4 per cent) within the first 3 months.…”
Section: Discussioncontrasting
confidence: 64%
“…Reports on the nutritional needs of patients with TCA are sparse 1,15,16 . The present study identified that supplementary nutrition was required commonly, even among patients with 0-20 cm of small bowel resected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Одним із дискусійних моментів при хірургічному лікуванні тотального агангліозу кишечника є використання поетапного підходу. В літературі описані одноетапні резекції товстої кишки з одночасним формуванням ілеоанального анастомозу [9,15]. Однак, після таких операцій досить часто з'являється неспроможність анастомозу та різного виду гнійно-септичні ускладнення, що в свою чергу стають причиною летальності.…”
Section: Vp Prytula 1 Dyu Krivchenya 1 MI Silchenko 2 Oounclassified